Gingival Hypertrophy in a Child with Hyaline Fibromatosis Syndrome - Predrag Knežević; Marko Tarle; Lucija Ida Fratrić; Antonia Tarle; Hana Knežević-Krajina; Darko Macan (University of Zagreb. School of Dental Medicine, 2020)
Hyaline fibromatosis syndrome (HFS) is a rare autosomal recessive genetic disorder characterized by accumulation of hyalinized fibrous tissue with cutaneous, mucosal, osteoarticular, and systemic involvement. The condition is caused by a mutation of ANTXR2 gene that results in a faulty synthesis of a transmembrane protein which leads up to excessive deposition of hyaline material in extracellular space. The first signs may be present at birth or appear during infancy, and joint stiffness is the first, most common, symptom. Other manifestations include joint contractures, hyperpigmented macules over bony prominences of the joints, and gingival hypertrophy. The symptom that raises suspicion of HFS is present later, along with subcutaneous growths. The progression of the disease includes enteropathy with extensive protein loss, chronic diarrhea and frequent infections. We present a case of a five-year-old girl with severe gingival hypertrophy that caused difficulties in eating and speaking. To the best of our knowledge, this is also the first patient in Croatia with a confirmed ANTXR2 gene mutation described in the literature.